Strategi Pencegahan Keterlambatan Proses Crew Change pada Armada Kapal PT. Satrya Maritim Indonesia - Raden Rendy Arman; Markus Asta Patma Nugraha; Irwan Jaya; Julita A. Gani; Muhammad Yusuf (Hengkara Majaya, 2026)
This research aims to analyze the factors causing delays in crew changes on the vessel fleet of PT. Satrya Maritim Indonesia and to formulate preventive strategies. The problem arose from cases of delayed crew rotations in the operational area of Brunei Darussalam, which resulted in client-imposed sanctions. The research method applied was qualitative descriptive, using observation, interviews, and documentation during the internship, as well as comparative analysis between field findings and crew management theories. The results indicate that delays were triggered by internal factors such as limited standby crew availability, irregular planning, weak interdepartmental coordination, and administrative errors, as well as external factors such as visa processing delays, changes in immigration policies, transportation disruptions due to weather, and specific client requirements. The recommended preventive strategies include the development of a structured timeline, strengthening the database and monitoring of both standby and former crew, regular recruitment, improved internal and external coordination, utilization of a crew management system, adjustment of rotation patterns, and continuous evaluation. In conclusion, preventing delays should focus on the synergy between human resource management, administrative planning, and compliance with destination country regulations in order to minimize risks of delays, enhance operational efficiency, and maintain client satisfaction. ABSTRAK Penelitian ini bertujuan menganalisis faktor penyebab keterlambatan crew change pada armada kapal PT. Satrya Maritim Indonesia dan merumuskan strategi pencegahannya. Permasalahan berawal dari kasus keterlambatan rotasi kru di wilayah operasi Brunei Darussalam yang berujung pada sanksi dari klien. Metode penelitian menggunakan deskriptif kualitatif melalui observasi, wawancara, dan dokumentasi selama praktik kerja, serta analisis perbandingan antara temuan lapangan dan teori manajemen kru. Hasil menunjukkan keterlambatan dipicu faktor internal seperti keterbatasan jumlah standby crew, ketidakteraturan perencanaan, lemahnya koordinasi antardepartemen, dan kesalahan administratif, serta faktor eksternal seperti keterlambatan pengurusan visa, perubahan kebijakan imigrasi, hambatan transportasi akibat cuaca, dan permintaan khusus klien. Strategi pencegahan yang direkomendasikan meliputi penyusunan timeline terstruktur, penguatan database dan monitoring kru standby maupun eks kru, rekrutmen berkala, peningkatan koordinasi internal-eksternal, pemanfaatan crew management system, penyesuaian pola rotasi, dan evaluasi berkelanjutan. Kesimpulannya, pencegahan keterlambatan harus berfokus pada sinergi manajemen sumber daya manusia, perencanaan administratif, dan kepatuhan regulasi negara tujuan guna meminimalkan risiko keterlambatan, meningkatkan efisiensi operasional, serta menjaga kepuasan klien.